PERENCANAAN BISNIS PENGERINGAN PALA DENGAN TEKNOLOGI OVEN DI KECAMATAN TAMANSARI KABUPATEN BOGOR - Monicha Septya Harni; Siti Jahroh (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2016)
Drying nutmeg companies rely on sunlight to dry the nutmeg. In fact, Bogor District has a high rainfall intensity. This condition can be overcome by using oven technology. By using oven technology, production process does not rely on the weather, the product will dry evenly, and does not require a large area. The purpose of this study is to analyze the business potential of nutmeg in Tamansari Sub-district and to design a business planbased on financial and non financial aspects. Interview was conducted to farmers and three nutmeg drying companies who were selected by snow ball sampling method. Other data were obtained from literature such as newspaper, internetand others. The results revealed that Tamansari Sub-district is an area that has the potential of natural resources, human resources, demand and marketing to develop business nutmeg. Price of dried seed was determined as Rp110 000 per kg and dried mace as Rp130 000 per kg. The target market is the export market. CV is chosen as the business form. NPV is Rp827 682 000, Net B/C3.83, IRR 67 per cent and payback period 1.92(1 year 9 months). BEP value is Rp108 248 600 in the first year and Rp372 745 700 in the next years. Business planning is feasible based on financial and non-financial analyses.